2016
DOI: 10.4338/aci-2016-06-le-0094
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Wearable Face-Mounted Computing Technology and the Effect on the DoctorPatient Relationship

Abstract: SummaryBackground Wearable face-mounted computers such as Google Glass™, Microsoft HoloLens™, and Oculus’ Rift®, are increasingly being tested in hospital care. These devices challenge social etiquette, raise privacy issues, and may disrupt the intimacy of the doctor patient relationship. We aimed to determine patients’ perception of and their privacy concerns with an archetype of wearable face-mounted computer devices, Google Glass.Methods Hospitalized inpatients were asked about their familiarity with Glass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Most patients are willing to have their doctor use face-mounted wearable computers, even when unfamiliar with the technology [ 49 ]. However, some patients have expressed concerns about privacy, which can certainly be a concern when a camera is pointing directly at them [ 49 ]. In this research, we serialized hand and audio data prior to network transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients are willing to have their doctor use face-mounted wearable computers, even when unfamiliar with the technology [ 49 ]. However, some patients have expressed concerns about privacy, which can certainly be a concern when a camera is pointing directly at them [ 49 ]. In this research, we serialized hand and audio data prior to network transmission.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine patient perceptions of FMT in an outpatient clinical setting; our findings build upon the work of Prochaska and colleagues [ 17 ] who examined patient perceptions of GG in a hospital setting. Although the primary reason FMT was implemented at our organization was to decrease charting documentation time and reduce clinician burnout, our results showed that FMT allowed providers to improve their interactions with patients.…”
Section: Discussionmentioning
confidence: 70%
“…Participants were asked to provide general demographic data, including gender, age, race, and education level. Following this, they completed a 12-item questionnaire, which was adapted from the questionnaire developed by Prochaska and colleagues [ 17 ], with added questions regarding the level of technology and privacy. The items assessed patient familiarity, comfort, and privacy level with FMT as well as their trust, relationship, and communication with their HCP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into stroke rehabilitation suggests that VR games can provide motivation, with patients controlling game play through therapy-related exercises (Patil 2017). Despite privacy concerns, one first step study found that patients were open to improved patient care through doctors' use of HMD (Prochaska et al 2016). Psychological issues such as phobias may be overcome through the use of VR exposure therapy (Coppens 2017), and the optical see-through display may lend itself to use in surgery (Qian et al 2017).…”
Section: Enhanced Accessibilitymentioning
confidence: 99%